Implementasi Sistem Monitoring dan Notifikasi Kualitas Udara Berbasis Internet of Things Menggunakan Arduino - Muhamad Muzakirin (Jurnal Jaringan Komputer dan Keamanan, 2021)
Air quality is a crucial factor affecting human health. Increased industrial activity, transportation, and population density have the potential to degrade air quality and elevate levels of hazardous pollutants, particularly carbon monoxide (CO). This study aims to implement an Internet of Things (IoT)-based air quality monitoring and notification system using Arduino. The system is designed with an MQ-7 sensor to detect CO gas and a DHT11 sensor to measure air temperature and humidity. Measurement data are sent to the ThingSpeak IoT platform, and notifications are delivered to users via the Telegram application. The system development method used was the prototype method. Data collection was conducted over seven days in March 2022 in Penukal Abab Lematang Ilir Regency. The measurement results showed that the highest average CO concentration, 9.99 ppm, occurred on March 7, 2022, at 4:41 PM WIB, while the lowest value, 1.83 ppm, occurred on March 1, 2022, at 10:34 AM WIB. The overall average concentration was 3.37 ppm, indicating that the air quality in Penukal Abab Lematang Ilir Regency remained within the good category.